Exploring Gut Microbial Dynamics and Symbiotic Interaction in Blattella germanica Using Rifampicin - Cazzaniga, Monica; Domínguez-Santos, Rebeca; Marín-Miret, Jesús; Gil, Rosario; Latorre, Amparo; García-Ferris, Carlos (Biology (Basel, Switzerland), 2023)
Blattella germanica harbours two cohabiting symbiotic systems: an obligate endosymbiont, Blattabacterium, located inside bacteriocytes and vertically transmitted, which is key in nitrogen metabolism, and abundant and complex gut microbiota acquired horizontally (mainly by coprophagy) that must play an important role in host physiology. In this work, we use rifampicin treatment to deepen the knowledge on the relationship between the host and the two systems. First, we analysed changes in microbiota composition in response to the presence and removal of the antibiotic with and without faeces in one generation. We found that, independently of faeces supply, rifampicin-sensitive bacteria are strongly affected at four days of treatment, and most taxa recover after treatment, although some did not reach control levels. Second, we tried to generate an aposymbiotic population, but individuals that reached the second generation were severely affected and no third generation was possible. Finally, we established a mixed population with quasi-aposymbiotic and control nymphs sharing an environment in a blind experiment. The analysis of the two symbiotic systems in each individual after reaching the adult stage revealed that endosymbiont’s load does not affect the composition of the hindgut microbiota, suggesting that there is no interaction between the two symbiotic systems in Blattella germanica.